Pengembangan Atraksi Wisata Minat Khusus Berbasis Nilai Tradisi Makotek Di Desa Wisata Munggu Badung Bali - Winda Kusumawati Supandi; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Makotek tradition is believed as a tradition to ward off bad omens which is practiced twice a year at Kuningan Day by Munggu villagers. In addition to the function of Makotek tradition as religious ritual, it also has a function as tourism attraction. This research aims to identify the value of Makotek tradition and gives some recommendation about tourism attraction development based on Makotek tradition value hence the stakeholder at Munggu Tourism Village can get additional reference to develop various tourism activities. This research uses qualitative method and applies tourism attraction concept, tourism attraction development concept, and special interest tourism concept. Makotek tradition value were: 1) presentations value of Makotek are talent value, skill value, and medium value; 2) content value of Makotek are knowledge value, ethnic value, intuition value, concept value, life value (morality value, social value, religion value); 3) appearance value of Makotek are form value (shape value and structure value). Special interest tourism attraction developments that can be done were: 1) develop attractions with something to see criteria that represents content value (knowledge and life value) of Makotek tradition and meets enriching and learning aspect; 2) develop attractions with something to do criteria that represents presentation value (skill, talent and medium value), content value (social, knowledge, intution, concept value), appearance value (shape and structure value) of Makotek tradition and meets rewarding, enriching, adventuring, and learning aspect; 3) develop attractions with something to buy criteria that represents presentation value (skill value) of Makotek Tradition and meets rewarding aspect. Keyword: Special Interest Tourism Attraction Development, Makotek Tradition Value, and Munggu Tourism Village